2017
DOI: 10.1371/journal.pone.0175190
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity on Prescription (PAP), in patients with metabolic risk factors. A 6-month follow-up study in primary health care

Abstract: There is strong evidence that inadequate physical activity (PA) leads to an increased risk of lifestyle-related diseases and premature mortality. Physical activity on prescription (PAP) is a method to increase the level of PA of patients in primary care, but needs further evaluation. The aim of this observational study was to explore the association between PAP-treatment and the PA level of patients with metabolic risk factors and the relationship between changes in the PA level and health outcomes at the 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 67 publications
0
65
2
1
Order By: Relevance
“…Although PAP has been associated with positive effects on metabolic risk factors, HR-QoL, and self-reported physical activity, 6,23 older patients might have difficulties achieving the recommended levels of physical activity. 24 Orrow et al 25 found that physical activity counseling in primary care did not increase physical fitness (assessed as VO 2max ), which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PAP has been associated with positive effects on metabolic risk factors, HR-QoL, and self-reported physical activity, 6,23 older patients might have difficulties achieving the recommended levels of physical activity. 24 Orrow et al 25 found that physical activity counseling in primary care did not increase physical fitness (assessed as VO 2max ), which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects of physical activity on prescription (PAP) have been reported on metabolic risk factors, HR-QoL, and self-reported physical activity. 6 In the last decade, PAP, together with motivational interviewing, has therefore been used by health professionals to counteract a low physical activity level, and to reduce the risk of cardiovascular morbidity and premature mortality. 7 PAP does, however not include any supervised exercise and is often prescribed without prior assessment of physical fitness in contrast to PTX.…”
Section: Introductionmentioning
confidence: 99%
“…The prescription programme in Sweden has shown impressive relative adherence and impact with a 17% dropout and significant improvement in PA for 73% of the cohort at 1 year follow-up. 30 Data from the Netherlands also indicate sustained adherence. 31 Yet data across other European countries show variance in scheme adherence and PA changes with most of the literature suggesting that that the UK has a particularly variable adherence level.…”
Section: Introductionmentioning
confidence: 99%
“…Dropout was related to sex (more female), musculoskeletal disorders, diastolic blood pressure and quality of life. No significant differences between followed up and dropouts were seen for age, socioeconomic factors, tobacco, and all other risk factors/diseases [13].…”
Section: Study Populationmentioning
confidence: 77%
“…The study population consisted of 444 patients from 15 primary health care centers in Gothenburg, Sweden, included during 2010-2014. The study design and medical results are presented in detail elsewhere [13]. The inclusion criteria were: being physically inactive, having at least one component of the metabolic syndrome present, receiving PAP treatment, and understanding the Swedish language.…”
Section: Study Populationmentioning
confidence: 99%